sentential logic derivations?

how do i prove the following is a theorem in SD

[(A -> B)->A]->A

... i started off by assuming [(A -> B)->A] then assume ~A to try to derive A in the end... but now i'm stuck :(

and also:

Suppose we dropped from SD the rule for vE, and adopted in its place the rule of Disjunctive Syllogism (DS), thus giving a modified system SD. Show that

you can derive the SD rule for vE in SD.

I have no idea how to even approach the second question.. any help would be greatly appreciated.. thanks! :D